MANAGING WOMEN EMPOWERMENT THROUGH PARTICIPATION IN SUSTAINABLE TOURISM DEVELOPMENT IN KAMPONG PHLUK, SIEM REAP, CAMBODIA - Nico Irawan; Vicheth Nara (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Tourism has been one of important Cambodia’s key economic growth drivers (OECD, 2018). After Khmer Rouge, most Cambodian women have become head of their families and indispensable part of the development in all sectors in Cambodia, including tourism. This study aims to explore how tourism influences on managing women empowerment and the participation of women in sustainable tourism development in Kampong Phluk community-based tourism site, Siem Reap, Cambodia. The qualitative descriptive approach with in-depth interviews, has been used for collecting data. The eighteen interviewees had at least 2 years’ experience in managing and participating in community-based tourism, especially female members. The constant comparison analysis is used to analyze data collected from the interviewees. The result revealed that tourism truly brings many socio-economic benefits to the local community, especially female members of the community by empowering them economically, socially, psychologically, and politically. This study also found that women are the key contributors to the development of sustainable tourism in their community by participating in all activities regarding economic sustainability, socio-cultural sustainability, and environmental sustainability, by managing the benefits from tourism and distributing them fairly to all people in the community but minimizing the negative impacts on the community’s natural resources plus preservation of the local culture.